Zinc and Copper Homeostasis in Head and Neck Cancer: Review and Meta-Analysis - Ressnerova, Alzbeta; Raudenska, Martina; Holubova, Monika; Svobodova, Marketa; Polanska, Hana; Babula, Petr; Masarik, Michal; Gumulec, Jaromir (Current Medicinal Chemistry, 2016)
Metals are known for playing essential roles in human physiology. Copper and zinc are trace elements closely dependent on one another and are involved in cell proliferation, growth, gene expression, apoptosis and other processes. Their homeostasis is crucial and tightly controlled by a resourceful system of transporters and transport proteins which deliver copper and zinc ions to their target sites. Abnormal zinc and copper homeostasis can be seen in a number of malignancies and also in head and neck cancer. Imbalance in this homeostasis is observed as an elevation or decrease of copper and zinc ions in serum or tissue levels in patients with cancer. In head and neck cancer these altered levels stand out from those of other malignancies which makes them an object of interest and therefore zinc and copper ions might be a good target for further research of head and neck cancer development and progression. This review aims to summarize the physiological roles of copper and zinc, its binding and transport mechanisms, and based on those, its role in head and neck cancer. To provide stronger evidence, dysregulation of levels is analysed by a meta-analytical approach.
Keywords: metallothionein